Treatment Of Leachate Landfill By Adsorption Using Charcoal Waste From Acetylene Gas Production - Rohaizad, Khairun Neesa (Universiti Sains Malaysia, 2021)
Landfill leachate forms via decomposition organic fractions in landfill by water percolating through the soil profile. Leachate contains high concentrations of dissolved and suspended organic matter, inorganic chemicals, and heavy metals as well as having both a high chemical oxygen demand (COD) and a high biological oxygen demand (BOD). The production of toxic leachates may pose a significant threat to the environment. Therefore, this study was conducted to determine the optimum treatment condition that influence the efficiency of adsorption process in treating landfill leachate. Adsorption is one of the most efficient ways used as high quality treatment processes for the removal of dissolved organic pollutants. In this study, charcoal from acetylene gas production (CAGP) was used as an adsorbent because it is a waste that can recycle and reuse. The CAGP was grind and sieve. The CAGP that passing 150um was used for adsorption study. The batch study was conducted based on one parameter at one time at different dose, shaking speed and contact time. Dosage used in this experiment is 10 g to 50 g. While speed is 50 rpm, 100 rpm, 150 rpm, 200 rpm and 250 rpm and time is 20 minutes, 40 minutes, 60 minutes, 80 minutes and 100 minutes. The optimum dose, speed and duration in order to remove are COD, colour and iron is 30 g of dose, 150 rpm of speed and 60 minutes of duration with the result of percentage removal is 51%, 52%, 48%, 55%, 61%, 41%, 75%, 75%, and 60% respectively. The preliminary results suggest that the performance of CAGP is acceptable as natural adsorbent for landfill leachate treatment. Further surface activation process might be required to enhance the capability of CAGP as an effective adsorbent. Therefore, the adsorption method by using CAGP to treat leachate is effective.